If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(x + -5) = 7 + -6(x + -2) Reorder the terms: 2x + -1(-5 + x) = 7 + -6(x + -2) 2x + (-5 * -1 + x * -1) = 7 + -6(x + -2) 2x + (5 + -1x) = 7 + -6(x + -2) Reorder the terms: 5 + 2x + -1x = 7 + -6(x + -2) Combine like terms: 2x + -1x = 1x 5 + 1x = 7 + -6(x + -2) Reorder the terms: 5 + 1x = 7 + -6(-2 + x) 5 + 1x = 7 + (-2 * -6 + x * -6) 5 + 1x = 7 + (12 + -6x) Combine like terms: 7 + 12 = 19 5 + 1x = 19 + -6x Solving 5 + 1x = 19 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + 1x + 6x = 19 + -6x + 6x Combine like terms: 1x + 6x = 7x 5 + 7x = 19 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 7x = 19 + 0 5 + 7x = 19 Add '-5' to each side of the equation. 5 + -5 + 7x = 19 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = 19 + -5 7x = 19 + -5 Combine like terms: 19 + -5 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 48-6x=4x | | 5x+6y=6y+5x | | (9/10)*(4/5) | | -5x=4y+8 | | n+6=-16 | | 6s+s-4s-3s+4s=16 | | X^2+y^2+3x-2y=0 | | 5=3-(4-2) | | -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= | | 70=164-v | | 6.78=2X/0.4-X | | 11x-67=77+2x |